Universal approach to light driven “superconductivity” via preformed pairs - Ke Wang; Zhiqiang Wang; Qijin Chen; K. Levin (npj Quantum Materials)
Abstract While there are many different mechanisms which have been proposed to understand the physics behind light induced “superconductivity”, what seems to be common to the class of materials in which this is observed are strong pairing correlations, which are present in the normal state. Here we argue, that the original ideas of Eliashberg are applicable to such a pseudogap phase and that with exposure to radiation the fermions are redistributed to higher energies where they are less deleterious to pairing. What results then is a photo-induced state with dramatically enhanced number of nearly condensed fermion pairs. In this phase, because the a.c. conductivity, σ(ω) = σ 1(ω) + i σ 2(ω), is dominated by the bosonic contribution, it can be computed using conventional (Aslamazov Larkin) fluctuation theory. We, thereby, observe the expected fingerprint of this photoinduced “superconducting” state which is a 1/ω dependence in σ 2 with fits to the data of the same quality as found for the so-called photo-enhanced (Drude) conductivity scenario. Here, however, we have a microscopic understanding of the characteristic low energy scale which appears in transport and which is necessarily temperature dependent. This approach also provides insight into recent observations of concomitant diamagnetic fluctuations. Our calculations suggest that the observed light-induced phase in these strongly paired superconductors has only short range phase coherence without long range superconducting order.